2020
DOI: 10.5435/jaaos-d-19-00271
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Nature of the Oncology Section of the Orthopaedic In-Training Examination

Abstract: Introduction: The Orthopaedic In-Training Examination (OITE) assesses orthopaedic resident knowledge over 275 multiple-choice questions.Since the first publication examining the contents of the pathology section was published over ten years ago, the pathology content has been renamed (oncology) and revamped. As the overall extent of these alterations is currently unknown, the efficacy of current orthopaedic oncology educational practices for optimal OITE performance should be questioned. To determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…12 This is consistent with a recent study of the Oncology domain of the OITE which demonstrated that the proportion of T1 questions decreased and the proportion of T3 questions increased from 2002 to 2006 and 2012 to 2016. 7 Another finding from this study is that approximately 34% of questions in the hand domain rely on at least 1 imaging modality or clinical photo, with clinical photos being the most common.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…12 This is consistent with a recent study of the Oncology domain of the OITE which demonstrated that the proportion of T1 questions decreased and the proportion of T3 questions increased from 2002 to 2006 and 2012 to 2016. 7 Another finding from this study is that approximately 34% of questions in the hand domain rely on at least 1 imaging modality or clinical photo, with clinical photos being the most common.…”
Section: Discussionmentioning
confidence: 73%
“…10,13 Each question was classified according to a well-described taxonomy classification. [3][4][5][6][7]14 Imaging modalities included radiography, computerized tomography, magnetic resonance imaging, ultrasound, pathology slide, other imaging modalities (eg, angiography), and clinical photographs. References were grouped into journal articles and books or textbooks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these publications focus on identifying numbers of questions, types of questions, topics, references used, and publication lag. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] This systematic review aims to assess all available studies that analyzed the types of questions in individual sections of the OITE. Currently, most relevant literature describes characteristics, references, and levels of evidence for individual sections of the examination.…”
mentioning
confidence: 99%
“… 1 , 2 , 7 8 9 10 11 12 13 14 OITE content undergoes frequent modifications to adhere to the advancing field of orthopaedics, and recent studies have been conducted to determine whether subspecialty content in the OITE changes over time; however, this has not been done for the musculoskeletal trauma section. 15 , 16 Our goal for this study was to analyze OITE musculoskeletal trauma questions from 2012 to 2019 and compare them with the results reported by Cross et al and Lackey et al from 2011.…”
mentioning
confidence: 99%